Konsep Manajemen Pengelolaan Pendidikan Bermutu di SMK Negeri 1 Tanjung Selor Kabupaten Bulungan Provinsi Kalimantan Utara - Sudarmin Sudarmin; A. Latief Arung Arafah; Siti Patimah; Andi Warisno (Journal on Education, 2024)
This examination expects to depict the administration idea of value training the executives in schools. The examination strategy utilized is a subjective enlightening technique, with information assortment procedures through meetings, perception and documentation studies. The examination results show that administration is a course of arranging, coordinating, driving and controlling the endeavors of hierarchical individuals where these four cycles have their separate capabilities to accomplish authoritative objectives. Dakam's endeavors to further develop schools should be possible with three activities: First, making schools better, Second, diminishing the weight. Third, changing over loads into energy. In Regulation no. 20 of 2003 concerning the Public School System Article 4 section 2 peruses: "Instruction is completed equitably, decently and non-unfairly by maintaining common freedoms, strict qualities, social qualities and public variety." To accomplish quality training, schools need to execute ten different ways. Working on the nature of training in schools is vital. By having a reasonable vision, fabricating a strong work group, further developing educator skill, doing customary management and assessment, using innovation, building associations with guardians and the local area, giving sufficient offices and framework, including understudies in direction, building school culture . positive. Aside from checking progress and praising accomplishments, school directors can establish a quality instructive climate and produce a skillful and cutthroat age.